Chromosomal organization of repetitive DNA sequences in Astyanax bockmanni (Teleostei, Characiformes): dispersive location, association and co-localization in the genome - Silva, Duílio M.Z.A. [UNESP]; Pansonato-Alves, José Carlos [UNESP]; Utsunomia, Ricardo [UNESP]; Daniel, Sandro Natal [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Oliveira, Claudio [UNESP]; Porto-Foresti, Fabio [UNESP]; Foresti, Fausto [UNESP] (Springer Nature, 2013)
Repetitive DNA sequences constitute a great portion of the genome of eukaryotes and are considered key components to comprehend evolutionary mechanisms and karyotypic differentiation. Aiming to contribute to the knowledge of chromosome structure and organization of some repetitive DNA classes in the fish genome, chromosomes of two allopatric populations of Astyanax bockmanni were analyzed using classic cytogenetics techniques and fluorescent in situ hybridization, with probes for ribosomal DNA sequences, histone DNA and transposable elements. These Astyanax populations showed the same diploid number (2n = 50), however with differences in chromosome morphology, distribution of constitutive heterochromatin, and location of 18S rDNA and retroelement Rex3 sites. In contrast, sites for 5S rDNA and H1, H3 and H4 histones showed to be co-located and highly conserved. Our results indicate that dispersion and variability of 18S rDNA and heterochromatin sites are not associated with macro rearrangements in the chromosome structure of these populations. Similarly, distinct evolutionary mechanisms would act upon histone genes and 5S rDNA, contributing to chromosomal association and co-location of these sequences. Data obtained indicate that distinct mechanisms drive the spreading of repetitive DNAs in the genome of A. bockmanni. Also, mobile elements may account for the polymorphism of the major rDNA sites and heterochromatin in this genus. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Cytogenetics; Evolution; FISH; Genome organization; Multigene families